Malocclusion and dental appearance in underprivileged Brazilian adolescents - Armando Koichiro KAIEDA; Jaqueline Vilela BULGARELI; Inara Pereira da CUNHA; Sílvia Amélia Scudeler VEDOVELLO; Luciane Miranda GUERRA; Gláucia Maria Bovi AMBROSANO; Antonio Carlos PEREIRA; Luiz Renato PARANHOS; Karine Laura CORTELLAZZI (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract Satisfaction with dental aesthetics is a subjective indicator used in epidemiological studies and is related to health behaviours. Little is known about the factors that influence this indicator, particularly among adolescents who live in a situation of social vulnerability. The aim of this study was to investigate the relationship between malocclusion and dental appearance in underprivileged Brazilian adolescents. This analytical cross-sectional study was conducted in Piracicaba, Brazil, and evaluated 884 adolescents from 13 to 19 years of age. The dependent variable was satisfaction with dental appearance, and the independent variables were classified as individual (components of the Dental Aesthetic Index - DAI, sex and age) and contextual (social exclusion index). For statistical analysis, multilevel regression models were estimated. The individual variables were considered Level 1, and the contextual variable was considered Level 2, with a level of significance of 5%. The mean age of the adolescents was 15.3 years. Female adolescents more frequently affirmed that they were satisfied with their dental appearance than did male individuals. There was an increase in dissatisfaction with oral health with the increase in anterior maxillary overjet, midline diastema, larger anterior irregularity in the maxilla, larger anterior irregularity in the mandible, anterior open bite and antero-posterior molar relation. Satisfaction with dental appearance was associated with individual factors such as sex and DAI components.